2022
DOI: 10.52964/amja.0904
|View full text |Cite
|
Sign up to set email alerts
|

Isolated paracetamol-induced acute kidney injury: a systematic review

Abstract: Aim: We sought to characterise the syndrome of isolated paracetamol-induced acute kidney injury (AKI), whose incidence and mechanisms are poorly understood. Methods: Using systematic review methodology, fifty-six papers relating to paracetamol-induced AKI were identified. Results: 24 cases of isolated paracetamol-induced AKI were identified and compared to 87 identified cases of concurrent renal and hepatic injury. Paracetamol-induced AKI became detectable 3-4 days after exposure; liver injury, where it occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
(68 reference statements)
0
0
0
Order By: Relevance
“…The incidence of isolated acute kidney injury (AKI) is unclear. It is very rare, ranging from 0.4 to 1.25% [ 2 ]. Many studies have demonstrated that large doses of paracetamol can cause kidney injury in rodent models [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The incidence of isolated acute kidney injury (AKI) is unclear. It is very rare, ranging from 0.4 to 1.25% [ 2 ]. Many studies have demonstrated that large doses of paracetamol can cause kidney injury in rodent models [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…AKI with paracetamol overdose is more common in adolescents and young adults, but the reason is unclear [ 6 ]. Isolated AKI has been observed to occur with an average age of 18.8 years [ 2 ]. An explanation could be that endoplasmic reticulum stress decreases with age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations